Pt crystalline ultrathin films as counter electrodes for bifacial dye-sensitized solar cells. (29th November 2016) - Cheng, Cheng-En; Lin, Zheng-Kun; Lin, Yu-Chang; Lei, Bi-Chen; Chang, Chen-Shiung; Chien, Forest Shih-Sen
Abstract: This study is to develop the Pt crystalline ultrathin films as high-transparent, efficient, and low-Pt-loaded counter electrodes (CEs) for bifacial dye-sensitized solar cells (DSCs). The 1-nm-thick Pt ultrathin films are sputtered on fluorine-doped tin oxide substrates and thermal annealed at 400 °C. After annealing, as-prepared amorphous-nanocrystal-mixed Pt films become high-crystalline films with better optical transmittance and electrocatalytic ability to I3 − reduction for bifacial DSCs. The rear-to-front ratios of short-circuit current density and power conversion efficiency of DSCs with crystalline ultrathin Pt CEs are as high as 81 and 83%, respectively.